Comparison of fresh and frozen ejaculated spermatozoa in sibling oocyte recipient cycles. Issue 2 (February 2022) - McCarter, Kelly; Setton, Robert; Chung, Alice; An, Anjile; Rosenwaks, Zev; Spandorfer, Steven
Abstract: Research question: Do IVF and intracytoplasmic sperm injection cycles using fresh and frozen ejaculated spermatozoa result in similar pregnancy outcomes in couples with non-male factor infertility? Design: Retrospective cohort study; patients undergoing donor egg recipient cycles, in which oocytes from a single ovarian stimulation were split between two recipients, were reviewed. Two recipients of oocytes from a single donor were paired and categorized based on the type of ejaculated spermatozoa (fresh/frozen). Outcomes included delivery rate, implantation, pregnancy, pregnancy loss and fertilization rates. Results: Of the 408 patients who received oocytes from a split donor oocyte cycle, 45 pairs of patients used discrepant types of ejaculated spermatozoa and were included in the study. Fertilization rate: fresh (74.8%); frozen (68.6%) ( P  = 0.13). Pregnancy rate: fresh (76%); frozen (67%); delivery rate: fresh (69%); frozen (44%); implantation rate was significantly higher: fresh (64%); frozen (36%) ( P  = 0.04). Rate of pregnancy loss was significantly higher in the frozen group compared with the fresh group (33% versus 5.9%, P  = 0.013). Adjusted odds for delivery was 67% lower in the frozen group (95% CI 0.12, 0.89). Adjusted odds of pregnancy (adjusted OR 0.67, 95% CI 0.20, 2.27) and implantation (adjusted OR 0.5, 95% CI 0.12, 2.12) were not significantly different between the frozen and fresh sperm groups. Conclusion: In this model that controls for oocyte quality by using paired recipients from the same donor, frozen ejaculated spermatozoa resulted in lower delivery rates than those using fresh spermatozoa